The Constitutional Court approves the Organic Law on the protection of citizen security (“Gag Law”): comment on STC 172/2020, of november 19th - Aba Catoira, Ana (Journal of the Basque Parliament, 2021)
In its Sentence 172/2020, of November 19 (Constitutional Challenge 2896-2015 presented by 97 deputies of PSOE; 11 from “Izquierda Plural” and “Chunta Aragonesista”; 4 from “Unión Progreso y Democracia” and 2 from the Mixed Group of the Congress of Deputies, challenging articles 19.2º, 20.2º, 36.2º and 23º, 37.1º in relation to articles 30.3º, 37.3º and 7º, as well as the first final provision of the Organic Law), the Plenary of the Constitutional Court has endorsed the constitutionality of Organic Law 4/2015, of March 30, on the Protection of Citizen Security (LOPSC,) approved by the PP in 2015 and known to its critics as “gag law”. The Judgment of the highest interpreter of the Constitution, of which the President of the Court, Juan José González Rivas, has been the speaker, dismisses most of the challenges confirming their constitutional adequacy except for the provision of the need for authorization to use images or data of authorities or members of the State Security Forces and Bodies, provided for in art. 36.23º of the Law. Since it is hidden from anyone, this resolution has special relevance because the LOPSC has been, since its approval, in the social and political spotlight, with the announced appeal of unconstitutionality that is now being resolved. And, this pronouncement of the High Court, which confirms the constitutionality of the contested precepts with the exception of the “authorization”, has not put an end to the confrontation of positions, since it has not had a peaceful reception, as expected.
Keywords: freedom; citizen security; electoral administration; sanction